Increased poly(ADP-ribosyl)ation of nuclear proteins in Alzheimer's disease. - Love, S; Barber, R; Wilcock, G (1999)
Experimental studies indicate that overactivation of the DNA repair protein poly(ADP-ribose) polymerase (PARP) in response to oxidative damage to DNA can cause cell death due to depletion of NAD+. Oxidative damage to DNA and other macromolecules has been reported to be increased in the brains of patients with Alzheimer's disease. In the present study we sought evidence of PARP activation in Alzheimer's disease by immunostaining sections of frontal and temporal lobe from autopsy material of 20 patients and 10 controls, both for PARP itself and for its end-product, poly(ADP-ribose). All of the brains had previously been subjected to detailed neuropathological examination to confirm the diagnosis of Alzheimer's disease or, in the controls, to exclude Alzheimer's disease-type pathology. Double immunolabelling for poly(ADP-ribose) and microtubule-associated protein 2 (MAP2), glial fibrillary-acidic protein (GFAP), CD68, A beta-protein or tau was used to assess the identity of the cells with poly(ADP-ribose) accumulation and their relationship to plaques and neurofibrillary tangles. Both PARP- and poly(ADP-ribose)-immunolabelled cells were detected in a much higher proportion of Alzheimer's disease (20 out of 20) brains than of control brains (5 out of 10) (P = 0.0018). Double-immunolabelling for poly(ADP-ribose) and markers of neuronal, astrocytic and microglial differentiation (MAP2, GFAP and CD68, respectively) showed many of the cells containing poly(ADP-ribose) to be neurons. Most of these were small pyramidal neurons in cortical laminae 3 and 5. A few of the cells containing poly(ADP-ribose) were astrocytes. No poly(ADP-ribose) accumulation was detected in microglia. Double-immunolabelling for poly(ADP-ribose) and tau or A beta-protein indicated that the cells with accumulation of poly(ADP-ribose) did not contain tangles and relatively few occurred within plaques. Our findings indicate that there is enhanced PARP activity in Alzheimer's disease and suggest that pharmacological interventions aimed at inhibiting PARP may have a role in slowing the progression of the disease.